Length‐weight relationships of four freshwater fishes from the JiangSu province, China. (18th October 2018) - Tang, Shengkai; Zhu, Binqing; Zhang, Tongqing; Xu, Fei; Mu, Huan; Wang, Hua
Abstract: Length‐weight relationships were determined for four freshwater fish species from Lake HongZehu, Lake GaoYouhu and the Yangtze River, China. Fish were sampled between June 2017 and May 2018 by fishermen, using various gears (e.g. cage nets, gillnets, trap nets and hand nets). Total length were measured (0.1 cm accuracy) and weights were determined (0.01 g accuracy). No information regarding the LWRs of these species was available in FishBase. New maximum total lengths for one species was also presented in this paper. Length and weight relationships are essential components in studies on fish biology and if undertaken regularly together with the determination of other parameters can be very helpful in fisheries management and species conservation.